How people learn: brain, mind, experience and school - Bransford, John; Brown, Ann (Washington,D.C.: National Academy Press, 2000)
Contents: Learners and learning,how experts differ from novices,learning and transfer,how children learn,teachers and teaching,the design of learning enviroments,effective teaching: example en history,mathematics and science,teacher learning,technology to support learning,futuro derection for the science of learning.
Include appendix
Keywords: Psicología Educativa